2006
DOI: 10.1097/01.sla.0000197738.63512.23
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Institutional Analysis of the Socioeconomic Determinants of Breast Reconstruction

Abstract: The reconstruction rate in this study (42%) is markedly higher than those previously reported. The type of insurance, education level, and employment status of a patient, but not her race or ethnicity, appear to influence the use of breast reconstruction. Because all patients were treated at an NCCN institution, these socioeconomic differences cannot be explained by access to care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
133
2
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 194 publications
(150 citation statements)
references
References 34 publications
12
133
2
3
Order By: Relevance
“…This compares favourably with rates of 16–59 per cent internationally3 8, 19 27, 28, 29, 30. The strongest predictors of PMBR cited were: age under 50 years; white race; higher income and education; and earlier disease stage31.…”
Section: Discussionmentioning
confidence: 75%
“…This compares favourably with rates of 16–59 per cent internationally3 8, 19 27, 28, 29, 30. The strongest predictors of PMBR cited were: age under 50 years; white race; higher income and education; and earlier disease stage31.…”
Section: Discussionmentioning
confidence: 75%
“…The eligibility criteria and data collection procedures for the database were described previously [17][18][19]. Briefly, clinical, treatment, and recurrence information is abstracted from medical records by dedicated and trained clinical research associates at each site.…”
Section: Data Sourcementioning
confidence: 99%
“…As with many other high-cost elective procedures, previous studies have demonstrated racial and socioeconomic variations in the utilization of post-mastectomy reconstruction. [1][2][3][4][5][6][7][8][9][10] Careful review of these studies suggests that the observed racial disparities likely reflect differences in socioeconomic status. In fact, the majority of studies that account for differences in individual SES find that race is not a significant predictor of reconstruction.…”
Section: Introductionmentioning
confidence: 99%